Radiological safety analysis of a newly designed spent resin mixture treatment facility during normal and abnormal operational scenarios for the safety of radiation workers - Jaehoon Byun; Seungbin Yoon; Hee Reyoung Kim (Nuclear Engineering and Technology, 2023)
The radiological safety of workers in a newly developed microwave-based spent resin treatment facility was assessed based on work location and operational scenarios. The results show that the remote-operation room worker was exposed to maximum annual dose of 3.19E+00 mSv, which is 15.9% of the dose limit, thereby confirming radiological safety. Inside the pathway, annual doses in the range of 7.87E-02–2.07E-01 mSv were measured initially at the mock-up tank and later at the point between the spent resin separation and treatment parts. The dose of emergency maintenance workers was below the dose limit (4.08E-03–4.99E+00 mSv); however, before treatment (separation and microwave), the dose of maintenance and repair workers exceeded the dose limit. The doses of the effluent removal workers at the zeolite and activated carbon storage tank and spent resin storage tank were the lowest at 2.79E-01–2.87E-01 mSv and 9.27E-01 mSv in “1 h” and “4–5 h of operation”, respectively. The immediately lower and upper layers of the facility room exhibited the highest annual doses of 1.84E+00 and 3.22E+00 mSv, respectively. Through this study, a scenario that can minimize the dose considering the movement of spent resin through the facility can be developed.